Joseph Ratzinger as Doctor of Incarnate Beauty - Tracey Rowland (Church, Communication and Culture, 2020)
This paper argues that Joseph Ratzinger is a theologian with the stature of a Church Doctor, notwithstanding the fact that he did not develop a theological system in the manner of other ‘big name’ theologians of the twentieth century such as Karl Barth, Karl Rahner and Hans Urs von Balthasar. The author argues that it is Ratzinger’s manner of responding to the contemporary crisis in fundamental theology that is his outstanding intellectual contribution to the life of the Church, along with his effect of a Christocentric turn in magisterial theology and his defence of beauty within his theology of culture.